Pelatihan Pembuatan SOP Bisnis yang Berbasis Hukum: Studi Penguatan Tata Kelola BUMDes di Desa Kedaton, Kabupaten Ogan Komering Ulu - Titie Syahnaz Natalia; Ega Anzani; Ribby Audia; Rahmat Rudiansyah (Asosiasi Periset Bahasa Sastra Indonesia, 2025)
This community service program was carried out with the primary objective of improving the institutional capacity of Village-Owned Enterprises (BUMDes) in Kedaton Village, Kedaton Peninjauan Raya District, Ogan Komering Ulu Regency. The focus of the activity was training and mentoring in the preparation of legally based Standard Operating Procedures (SOPs), in order to strengthen village business governance in a participatory and sustainable manner. The method used was a participatory approach, involving village officials and the local community in every stage of the activity, from identifying institutional problems, preparing SOP documents, to evaluation and follow-up. This activity was carried out through workshops, focus group discussions, and technical mentoring, so that participants not only received theoretical material but also actively participated in preparing and implementing SOPs relevant to the needs of the BUMDes. The results of the activity showed a significant increase in legal awareness among BUMDes managers and the village community. In addition, a new institution was formed in the form of a Village SOP Team that plays a driving role in the process of preparing and supervising the implementation of SOPs. Local leaders who have a concern for business governance and village community empowerment also emerged. The development of SOPs not only strengthens the administrative aspects of Village-Owned Enterprises (BUMDes) but also encourages social transformation. Communities become more involved in decision-making and develop a sense of ownership of village businesses. These findings indicate that integrating a legal approach into community empowerment practices can be an effective strategy for increasing accountability, transparency, and the future sustainability of village businesses.